Analisis Pengaruh Kemiskinan, Indeks Pembangunan Manusia (IPM) Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Sumatera Selatan - Putri, Dita Marisa (LPPM Universitas Muhammadiyah Mamuju, 2023)
The development of a country cannot be separated from the role of regional government, which is an equally important part of maximizing the potential resources contained therein. This research aims to determine the influence of Poverty, Human Development Index (HDI), and Labor on Economic Growth in East Java. The method used is a quantitative method with multiple regression analysis and time series data. Simultaneously, Poverty, Human Development Index (HDI), and Labor together have a positive and significant effect on Economic Growth in East Java. Partially, the Poverty variable has a positive and significant effect on Economic Growth in South Sumatra, while the Human Development Index (HDI) and Labor variables have a negative and significant effect on Economic Growth in South Sumatra.